An EHMT2/NFYA-ALDH2 signaling axis modulates the RAF pathway to regulate paclitaxel resistance in lung cancer - Wenjing Wang; Jianmin Wang; Shuai Liu; Yong Ren; Jingyu Wang; Sen Liu; Wei Cui; Lina Jia; Xing Tang; Jingyu Yang; Chunfu Wu; Lihui Wang (Molecular Cancer, 2022)
Abstract Background Lung cancer is a kind of malignancy with high morbidity and mortality worldwide. Paclitaxel (PTX) is the main treatment for non-small cell lung cancer (NSCLC), and resistance to PTX seriously affects the survival of patients. However, the underlying mechanism and potential reversing strategy need to be further explored. Methods We identified ALDH2 as a PTX resistance-related gene using gene microarray analysis. Subsequently, a series of functional analysis in cell lines, patient samples and xenograft models were performed to explore the functional role, clinical significance and the aberrant regulation mechanism of ALDH2 in PTX resistance of NSCLC. Furthermore, the pharmacological agents targeting ALDH2 and epigenetic enzyme were used to investigate the diverse reversing strategy against PTX resistance. Results Upregulation of ALDH2 expression is highly associated with resistance to PTX using in vitro and in vivo analyses of NSCLC cells along with clinicopathological analyses of NSCLC patients. ALDH2-overexpressing NSCLC cells exhibited significantly reduced PTX sensitivity and increased biological characteristics of malignancy in vitro and tumor growth and metastasis in vivo. EHMT2 (euchromatic histone lysine methyltransferase 2) inhibition and NFYA (nuclear transcription factor Y subunit alpha) overexpression had a cooperative effect on the regulation of ALDH2. Mechanistically, ALDH2 overexpression activated the RAS/RAF oncogenic pathway. NSCLC/PTX cells re-acquired sensitivity to PTX in vivo and in vitro when ALDH2 was inhibited by pharmacological agents, including the ALDH2 inhibitors Daidzin (DZN)/Disulfiram (DSF) and JIB04, which reverses the effect of EHMT2. Conclusion Our findings suggest that ALDH2 status can help predict patient response to PTX therapy and ALDH2 inhibition may be a promising strategy to overcome PTX resistance in the clinic.